Organization and Structure of the Antigraph of the Songbooks of the National Library and the Vatican Library - Monteagudo, Henrique (Madrygal. Revista de Estudios Gallegos, 2023)
The present contribution focuses on the antigraph of B and V, that is, the General Compilation of Galician-Portuguese Troubadour Lyric, with the aim of analysing its organisation and its material structure. As to the organization, it is based on the research of Michaëlis de Vasconcellos, Tavani and Resende de Oliveira, complemented with the results obtained by the author in his previous works on scriptural-linguistic variation and textual stratigraphy. A proposal for the reconstruction of the configuration of the codex, lost since the 15th century, is presented. A codicological analysis of the testimonies derived from it is carried out, in particular, of the apographers B and V themselves. This analysis is based on the contributions of D’ Heur on V and Ferrari on B, but progress is made through the combined study of both codices and the information on fasciculation and foliation of the antigraph that they offer. The conclusions summarize the results achieved as to the arrangement of the compositions in the original codex, the procedures for incorporating new materials and the underlying operations of integration, revision, and rearrangement. The results achieved represent a substantial progress in the knowledge of the process of constitution the manuscript tradition of Galician-Portuguese troubadour lyric.